Design of a solar powered LED street light: effect of panel's mounting angle and traffic sensing - Ahmed, Sanjana; Zenan, Ahmed Hosne; Tasneem, Nisat; Rahman, Dr. Md. Mosaddequr (© 2013 IEEE Computer Society, 2016)
This conference paper was presented in the 2013 IEEE Conference on Sustainable Utilization and Development in Engineering and Technology, IEEE CSUDET 2013; Selangor; Malaysia; 30 May 2013 through 31 May 2013 [© 2013 IEEE Computer Society] The conference paper's definite version is available at: http:// 10.1109/CSUDET.2013.6670990